2016
DOI: 10.1002/2015jd024179
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of lightning NOx production based on OMI NO2 observations over the Gulf of Mexico

Abstract: We evaluate nitrogen oxide (NO x = NO + NO 2 ) production from lightning over the Gulf of Mexico region using data from the Ozone Monitoring Instrument (OMI) aboard NASA's Aura satellite along with detection efficiency-adjusted lightning data from the World Wide Lightning Location Network (WWLLN). A special algorithm was developed to retrieve the lightning NO x (LNO x ) signal from OMI. The algorithm in its general form takes the total slant column NO 2 from OMI and removes the stratospheric contribution and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
153
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(163 citation statements)
references
References 93 publications
4
153
2
Order By: Relevance
“…7), it has also been applied to NO 2 with OMI to derive information about its concentration in the free troposphere (Choi et al, 2014;Belmonte Rivas et al, 2015). In addition, other approaches have been applied to isolate NO 2 generated from lightning Pickering et al, 2016).…”
Section: No 2 Cloud Slicingmentioning
confidence: 99%
“…7), it has also been applied to NO 2 with OMI to derive information about its concentration in the free troposphere (Choi et al, 2014;Belmonte Rivas et al, 2015). In addition, other approaches have been applied to isolate NO 2 generated from lightning Pickering et al, 2016).…”
Section: No 2 Cloud Slicingmentioning
confidence: 99%
“…Recent research has shown that satellite measurements are a useful tool for estimating LNO x (Boersma et al, 2005;Beirle et al, 2010;Bucsela et al, 2010;Pickering et al, 2016). Pickering et al (2016) combined OMI V trop data with data from the World Wide Lightning Location Network (WWLLN) (Dowden et al, 2002;Lay et al, 2004;Virts et al, 2013) to estimate the production efficiency (PE) of LNO x (moles per flash). Using SPv2 and WWLLN data from the Gulf of Mexico over five Northern Hemisphere summers (2007)(2008)(2009)(2010)(2011), they obtained a mean PE value of 80 ± 45 mol flash −1 .…”
Section: Impact On Lightning No X Emissions Estimatementioning
confidence: 99%
“…Satellite instruments measure the absorption of solar backscatter in the UVvisible spectral range, enabling estimation of the amount of NO 2 in the atmosphere between the instrument and the surface. By comparing observed spectra with a reference spectrum, we can derive total column amounts; this technique is called differential optical absorption spectroscopy (DOAS) (Platt, 1994).…”
Section: Introductionmentioning
confidence: 99%